Complementaridade entre o lean manufacturing e o quick response manufacturing : estudos de casos - Gómez Paredes, Fernando José (Universidade Federal de São Carlos, 2016)
Operations Management Researchers have largely studied and analyzed Lean Manufacturing (LM), by its capacity of productivity improvement in industry. Even so, this approach has found several difficulties to deal with all production types, especially those that have high-variety and low-volume. Therefore, LM has been integrated with other approaches to maximize its action, like Quick Response Manufacturing (QRM). However, few researchers have studied the integration of LM and QRM. In the aim of solving this gap, this research studies how QRM complements LM in high-variety production, in order to extend improvements with the integration of the two approaches. This research used multiple case study method to determine the behavior of the two approaches inside high-variety production. Two companies were analyzed, where the approaches supplied some improvement proposals to find complimentary elements. Data were collected throughout interviews, document analyzes and observation. As main result, QRM inserts concepts of System Dynamics as a compliment of Lean. Thus, tools as simulation, lead-time treatment, and analysis of utilization are the easiest for incorporation in the opportunities of improvement. A tool proposed based in unification of Value Stream Map (VSM) and Manufacturing Critical-Path Time (MCT) detects waste using the approaches, optimizing them. Future research should focus on using the integration proposed, verifying if compliments are successful in other flow and type production.
Keywords: Manufatura enxuta; Quick response manufacturing; Lead time; Alta variedade; Integração MFV MCT; Lean manufacturing; High variety; MCT; VSM; Integration; ENGENHARIAS::ENGENHARIA DE PRODUCAO